The description of a new species Polymastigos javaensis n.sp. (Annelida: Capitellidae) from the Segara Anakan mangroves, Central Java, Indonesia - Pamungkas, Joko (Zootaxa, 2015)
A new species, Polymastigos javaensis n. sp., is described from sandy clay sediment (0-30 cm depth) of the Segara Anakan mangroves. The species is described based on the distribution of capillaries and hooks, and the form of the prostomium, thorax, abdomen, lateral organs, genital pores, branchiae and pygidium. Methyl green staining pattern was applied to examine the similarity between the material of this study and Green’s material. Polymastigos javaensis n. sp. is the second species belonging to the genus Polymastigos, after P. reishi Green, 2002. It differs from P. reishi in the form of abdominal segments and hooks, and the methyl green staining pattern. A key to distinguish the two species is provided in this paper.